Carbonate and silicate weathering in two presently glaciated, crystalline catchments in the Swiss Alps - Hosein, Rachel; Arn, Kaspar; Steinmann, P.; Adatte, Thierry; Föllmi, Karl B. (My University, 2004)
We present a weathering mass balance of the presently glaciated Rhône and Oberaar catchments, located within the crystalline Aar massif (central Switzerland). Annual chemical and physical weathering fluxes are calculated from the monthly weighted means of meltwater samples taken from July, 1999 to May, 2001 and are corrected for precipitation inputs. The meltwater composition issuing from the Oberaar and Rhône catchments is dominated by calcium, which represents 81% and 55% of the total cation flux respectively (i.e. 555 and 82–96 keq km−2 yr−1). The six to seven times higher Ca2+ denudation flux from the Oberaar catchment is attributed to the presence of a strongly foliated gneissic zone. The gneissic zone has an elevated calcite content (as reflected by the 4.6 times higher calcite content of the suspended sediments from Oberaar compared to Rhône) and a higher mechanical erosion rate (resulting in a higher flux of suspended sediment). The mean flux of suspended calcite of the Oberaar meltwaters during the ablation period is 7 times greater than that of the Rhône meltwaters. Taking the suspended calcite as a proxy for the total (including sub-glacial sediments) weathering calcite surface area, it appears that the available surface area is an important factor in controlling weathering rates. However, we also observe an increased supply of protons for carbonate dissolution in the Oberaar catchment, where the sulphate denudation flux is six times greater. Carbonic acid is the second important source of protons, and we calculate that three times as much atmospheric CO2 is drawn down (short term) in the Oberaar catchment. Silica fluxes from the two catchments are comparable with each other, but are 100 kmol km2 yr−1 lower than fluxes from physically comparable, non-glaciated basins.